An Historical Sketch of the Knights of Labor - Wright, Carroll D. (Quarterly Journal of Economics, 1887)
An Historical Sketch of the Knights of Labor Get access Carroll D. Wright Carroll D. Wright Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 1, Issue 2, January 1887, Pages 137–168, https://doi.org/10.2307/1880768 Published: 01 January 1887